2021
DOI: 10.1590/2175-7860202172016
|View full text |Cite
|
Sign up to set email alerts
|

In vitro culture of sempre-vivas species (Comanthera): a review

Abstract: The term “sempre-viva” denotes plants whose structures retain their natural form and color after being cut and dried. For these reasons, they are commercially valuable for ornamental purposes. However, due to extractive overexploitation of their inflorescences, some of these species are considered endangered. The genus Comanthera includes the sempre-vivas species with greatest economic importance in Brazil. Previous studies have shown that tissue culture is a workable strategy for in vitro propagation and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Rooting is one of the limiting steps for the propagation of "evergreens" due to the low response of plants to the formation of roots in vitro. Previous investigations showed that the use of auxin is not efficient for inducing root growth of C. mucugensis [3], which contributes to the low success of ex vitro cultivation. In the present study, the type of medium gelling did not promote a significant difference in the induction and root characteristics of the shoots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rooting is one of the limiting steps for the propagation of "evergreens" due to the low response of plants to the formation of roots in vitro. Previous investigations showed that the use of auxin is not efficient for inducing root growth of C. mucugensis [3], which contributes to the low success of ex vitro cultivation. In the present study, the type of medium gelling did not promote a significant difference in the induction and root characteristics of the shoots.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the species is considered to be at high risk of extinction in the wild [2]. The growth of C. mucugensis occurs under restricted environmental conditions, which makes it difficult to establish ex situ cultures and makes plant tissue culture the main technique for cultivation and propagation of the species [3]. However, this is a very expensive method of ex situ conservation and many germplasm collections can have low genetic variability [4].…”
Section: Introductionmentioning
confidence: 99%